A microfluidic approach to micromembrane synthesis for complex release profiles of nanocarriers. Issue 6 (26th February 2020) - Jia, Nan; Rosella, Erica; Juère, Estelle; Pouliot, Roxane; Kleitz, Freddy; Greener, Jesse
Abstract : Physically crosslinked layered microscale biomembranes from pure chitosan are demonstrated for pH-triggered release functionalized mesoporous silica nanoparticles. The work opens the door to synthesis of complex nano-enhanced micro membranes. Abstract : Physically crosslinked microscale biomembranes synthesized from pure chitosan are designed and demonstrated for pH-triggered release of embedded functionalized mesoporous silica nanoparticles. Nanoparticle-loaded membranes are formed in a microfluidic channel at the junction between accurately controlled co-flowing streams to achieve highly tuneable membrane properties. After formation, the loaded membranes remain stable until contact with physiological acidic conditions, resulting in controlled nanoparticle release. Furthermore, nanoparticle-loaded membranes with complex layered architectures are synthesized using different flow schemes, thus enabling customized nanoparticle release profiles. These novel materials are well-suited for integration within small medical devices as well as off-chip applications.